Cued Memory Reactivation During SWS Abolishes the Beneficial Effect of Sleep on Abstraction. Issue 8 (5th July 2017) - Hennies, Nora; Lambon Ralph, Matthew A; Durrant, Simon J; Cousins, James N; Lewis, Penelope A
Abstract: Study Objectives: Extracting regularities from stimuli in our environment and generalizing these to new situations are fundamental processes in human cognition. Sleep has been shown to enhance these processes, possibly by facilitating reactivation-triggered memory reorganization. Here, we assessed whether cued reactivation during slow wave sleep (SWS) promotes the beneficial effect of sleep on abstraction of statistical regularities. Methods: We used an auditory statistical learning task, in which the benefit of sleep has been firmly established. Participants were exposed to a probabilistically determined sequence of tones and subsequently tested for recognition of novel short sequences adhering to this same statistical pattern in both immediate and delayed recall sessions. In different groups, the exposure stream was replayed during SWS in the night between the recall sessions (SWS-replay group), in wake just before sleep (presleep replay group), or not at all (control group). Results: Surprisingly, participants who received replay in sleep performed worse in the delayed recall session than the control and the presleep replay group. They also failed to show the association between SWS and task performance that has been observed in previous studies and was present in the controls. Importantly, sleep structure and sleep quality did not differ between groups, suggesting that replay during SWS did not impair sleep but rather disrupted or interfered with sleep-dependent mechanisms that underlie the extraction of the statistical pattern. Conclusions: These findings raise important questions about the scope of cued memory reactivation and the mechanisms that underlie sleep-related generalization.